2023
DOI: 10.1111/pace.14707
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle branch area pacing prevents pacing induced cardiomyopathy in long‐term observation

Abstract: Background: Left bundle branch area pacing (LBBAP) is one of the methods to deliver conduction system pacing which potentially avoids the negative impact of conventional right ventricular pacing.Objective: To assess echocardiographic outcomes in a long-term observation in patients with LBBAP implemented for bradyarrhythmia indications. Methods and Results:A total of 151 patients with symptomatic bradycardia and LBBAP pacemaker implanted, were prospectively included in the study. Subjects with left bundle branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Bednarek et al [ 10 ] showed that LVEF increased in bradycardia patients with baseline LVEF below 50%, while it was stable in individuals with preserved LVEF, and they concluded that LBBAP prevents PICM in patients with preserved LVEF and improves left ventricle function in subjects with depressed LVEF. Our results are, in general, consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bednarek et al [ 10 ] showed that LVEF increased in bradycardia patients with baseline LVEF below 50%, while it was stable in individuals with preserved LVEF, and they concluded that LBBAP prevents PICM in patients with preserved LVEF and improves left ventricle function in subjects with depressed LVEF. Our results are, in general, consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying these results is fast activation of the left ventricle by left bundle branch (LBB) fibres or via quick capture of the left side of the septal myocardium. This may not only prevent the development of pacing-induced cardiomyopathy [ 10 , 11 ], but may also improve ventricular synchrony, restoring impaired conduction in patients with left bundle branch block (LBBB). Individuals with right bundle branch block (RBBB) may benefit from a reduction in right ventricular activation delay due to the capture of the septal myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Long term observational trials have demonstrated that left bundle area pacing preserves EF. 16 Small, retrospective studies have also show benefit in improving EF in patients who have already developed PICM. 17 Although prospective randomized trials are still needed, left bundle area pacing is becoming standard practice.…”
Section: Discussionmentioning
confidence: 99%
“…Like us, Jastrzębski et al [5] concluded that there is no influence of operator experience on LBBP and LVSP proportions. The high success rate of LBBAP is encouraging for wide application of this method, especially when the recent study of Bednarek et al [11] showed that LBBAP could prevent pacing-induced cardiomyopathy.…”
Section: Success Rates Of Lbbap and Lbbpmentioning
confidence: 98%